Neuron-Astrocyte Crosstalk: The Never-Ending Story Of Α-Synuclein And Lipid Metabolism - Bonjour, Mariel (2025)
In our laboratory, we have previously demonstrated that mild overexpression of α-synuclein in neurons induces a shift in lipid metabolism, promoting lipid droplet and cholesterol accumulation, along with the downregulation of phospholipase D1 (PLD1) and cytoskeletal rearrangements. Additionally, we showed that lipid droplets are essential for neuronal survival under conditions of α-synuclein overexpression. In this study, we aimed to characterize how neuronal α-synuclein overexpression impacts astrocyte biology and metabolism. To this end, we used various glial culture models: mixed primary glia, primary astrocytes, and the C6 astrocytic cell line. These cultures were treated with neuronal conditioned media derived from cells expressing endogenous levels of α-synuclein (e-aSyn CM) or overexpressing α-synuclein (oe-aSyn CM). Both conditions were compared to cultures incubated with regular medium (control). We found that astrocytes exposed to oe-aSyn CM exhibited increased lipid droplets and cholesterol content with the upregulation of diacylglycerol O-acyltransferase expression. Remarkably, these astrocytes also showed an upregulation of PLD1. These metabolic changes were accompanied by actin cytoskeletal rearrangements. Moreover, exposure to oe-aSyn CM also modulated astrocyte proliferative and migratory behavior. Our findings indicate that neuronal α-synuclein overexpression modulates astrocytic lipid metabolism and cytoskeletal architecture and may also affect proliferation and glial scar.